Faktor-Faktor Yang Mempengaruhi Persistensi Laba Pada Perusahaan Manufaktur - Rohit, Rohit; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2021)
: The purpose of this research is to obtain empirical evidence about the effects of accruals, operating cash flows, firm size, and leverage on earnings persistence in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. This research used 61 samples and 232 data from manufacturing companies selected by the purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and processed using the Eviews 9.0 program. The result of this research indicate that operating cash flow has a positive and significant effect on earnings persistence while accruals, firm size, and leverage have no significant effect on earnings persistence.